Barriers and solutions of promoting tax culture in Iran’s sports - Kiani, Mohammad Saeid (Journal of Education, Health and Sport, 2019)
Tax culture means attitudes, approaches, social values, current regulations and level of people’s knowledge about tax. Excessive commercialization of sports and its popularity along with lack of a concise and integrated tax system have made the issue of tax a complicated matter. There are some evidence about tax evading in sport by athletes and clubs in the country. Considering the role of tax as one of the main resources of governments in economic stability and not relying too much to national resources, especially in developed countries, this research executed to indentify barriers and solutions of promoting tax culture in sport in Iran.